Investigating the Correlation Among Social Media Marketing, Electronic Word-Of-Mouth, Celebrity Endorsements, and Consumer’s Purchase Intention of Cosmetic Products - Halid, Nur Farrah Mohammad; Tajuddin, Nur Akmal Ahmad; Abas, Zahidatun Najah Md; Yusof, Yuslina Liza Mohd (Advances in Social Sciences Research Journal, 2024)
Instagram is one of the most popular and fastest-growing social commerce platforms among Gen Y, as it allows users to browse online shops by using visual interface on a mobile device. They are also used to shopping online using this platform. Most cosmetic products company adapting social media marketing by promoting products using social commerce such as and Instagram. Thus, the purpose of this study is to empirically investigate the relationship between social media marketing, electronic word of mouth, celebrity endorsement, and purchase intention on social commerce of cosmetic products in Malaysia. The unit of analysis is individual that was more likely to buy when they were exposed to social media marketing, electronic word-of-mouth, and celebrity endorsement on social commerce which was Instagram. The descriptive statistics analysis was applied to describe the different characteristics of the respondents. The study's outcomes demonstrated a noteworthy and affirmative connection between consumers' purchase intention and social media marketing, electronic word of mouth, along with celebrity endorsement. This research centers around three pivotal variables: social media marketing, electronic word of mouth, and celebrity endorsement. The conclusions drawn from this study can serve as valuable pointers for enhancing the realm of social commerce among cosmetic product marketers. This study holds significance in its exploration of the determinants impacting consumers' purchase intent for cosmetic products. Furthermore, it furnishes cosmetic product marketers with a set of four strategic recommendations to enhance their social commerce endeavor. The recommendations encompass the utilization of customer testimonials/reviews sharing, collaboration with celebrities or influencers of diverse backgrounds, staying abreast of developments in social media, augmented reality (AR), and artificial intelligence (AI).